P26 Socioeconomic and gendered inequities in travel behaviour in Africa: mixed-method systematic review and meta-ethnography. (26th August 2022) - Foley, Louise; Brugulat-Panés, Anna; Woodcock, James; Govia, Ishtar; Hambleton, Ian; Turner-Moss, Eleanor; Mogo, Ebele; Awinja, Alice Charity; Dambisya, Philip; Matina, Sostina Spiwe
Abstract : Background: Travel has individual, societal and planetary health implications. We explored socioeconomic and gendered differences in travel behaviour in Africa, to develop an understanding of travel-related inequity. Methods: We conducted a mixed-methods systematic review (PROSPERO CRD42019124802). In 2019, we searched MEDLINE, TRID, SCOPUS, Web of Science, LILACS, SciELO, Global Health, Africa Index Medicus, CINAHL and MediCarib for studies examining travel behaviour by socioeconomic status and gender in Africa. We appraised study quality using Critical Appraisal Skills Programme checklists. We synthesised qualitative data using meta-ethnography, followed by a narrative synthesis of quantitative data, and integrated qualitative and quantitative strands using pattern matching principles. The review was conducted through a global public health research network (https://gdarnet.org/). In this project, we aspired to forge equitable partnerships though the provision of bespoke systematic review training to junior team members; multiple rounds of co-interpretation of findings and co-production of their meaning; and transparent and inclusive authorship opportunities. Results: We retrieved 103 studies (20 qualitative, 24 mixed-methods, 59 quantitative). From the meta-ethnography, we observed that travel is: intertwined with social mobility; necessary to access resources; associated with cost and safety barriers; typified by long distances and slow modes; and dictated by gendered social expectations. We also observed that: motorised transport is needed in cities; walking is an unsafe, 'captive' mode; and urban and transport planning are uncoordinated. From these observations, we derived hypothesised patterns that were tested using the quantitative data, and found support for these overall. In lower socioeconomic individuals, travel inequity entailed reliance on walking and paratransit (informal public transport), being unable to afford travel, travelling less overall, and travelling long distances in hazardous conditions. In women and girls, travel inequity entailed reliance on walking and lack of access to private vehicles, risk of personal violence, societally-imposed travel constraints, and household duties shaping travel. Limitations included lack of analytical rigour in qualitative studies and a preponderance of cross-sectional quantitative studies (offering a static view of an evolving process). Discussion: Overall, we found that travel inequity in Africa perpetuates socioeconomic and gendered disadvantage. Proposed solutions focus on improving the safety, efficiency and affordability of public transport and walking. Through the conduct of this systematic review, we reflect on the strengths and challenges of collaborative research in the global health arena.